2021
DOI: 10.52586/5026
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, atherosclerosis, arterial imaging, cardiovascular risk stratification, and manifestations in COVID-19 framework: a narrative review

Smiksha Munjral,
Puneet Ahluwalia,
Ankush D. Jamthikar
et al.

Abstract: Background: Atherosclerosis is the primary cause of the cardiovascular disease (CVD). Several risk factors lead to atherosclerosis, and altered nutrition is one among those. Nutrition has been ignored quite often in the process of CVD risk assessment. Altered nutrition along with carotid ultrasound imaging-driven atherosclerotic plaque features can help in understanding and banishing the problems associated with the late diagnosis of CVD. Artificial intelligence (AI) is another promisingly adopted technology f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 271 publications
(300 reference statements)
0
10
0
Order By: Relevance
“…It is suggested that vasculitis and thrombosis of the aortic vasa vasorum may represent key factors linking severe forms of SARS-CoV-2 infection with transformation of a stable plaque into an unstable lesion with thromboembolic consequences [63]. The impact of SARS-CoV-2 on large vessels such as the aorta is more complex than has been previously considered.…”
Section: Microvascular Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that vasculitis and thrombosis of the aortic vasa vasorum may represent key factors linking severe forms of SARS-CoV-2 infection with transformation of a stable plaque into an unstable lesion with thromboembolic consequences [63]. The impact of SARS-CoV-2 on large vessels such as the aorta is more complex than has been previously considered.…”
Section: Microvascular Dysfunctionmentioning
confidence: 99%
“…Direct cytopathic effect of the virus on endothelial cells [69] Protease activation, causing a transition from a stable to a pathological atherosclerotic injury and the degradation of the plaque protective fibrous cap. [9,42] Leucocyte recruitment and adhesion to the vascular wall [12] Expression of pro-inflammatory chemokines and cytokines (CXCL1, CXCL2, CXCL3, CXCL8, IL-1β) in the vascular wall resulted from the activation of MyD88-dependent pathways [1,34] VEGLX damage [36] Mitochondrial dysfunction leading to the increased production of reactive oxygen species [33] Endothelial damage caused by neutrophil extracellular traps (NETs) [53] Endothelial damage caused by the components of the activated complement system [52] Vasa vasorum vasculitis and/or thrombosis [63] Interestingly, pharmacological agents commonly used in the treatment of atherosclerosis, such as statins and acetylsalicylic acid, seem to reduce both the incidence of serious complications of COVID-19 and the death rate from this infection. The possible effects of chronic therapy with acetylsalicylic acid have not been fully studied.…”
Section: Mechanismsmentioning
confidence: 99%
“…[ 13 , 14 ] Additionally, COVID-19 symptoms promote malnutrition, and its presence is associated with higher mortality and longer hospital stays. [ 15 17 ] The prognostic nutritional index (PNI) is an effective indicator that reflects COVID-19 severity and mortality. [ 18 ] Therefore, this study will be the first to construct a combination of nutritional and kidney function indicators to determine whether they can better predict disease progression than individual predictors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to GSM, the presence of carotid plaque is associated with the incidence of CVD events [ 29 , 30 ] and is further an established ultrasound surrogate of CVD [ 31 , 32 ]. Nutritional aspects are known to play a relevant role in the development of atherosclerosis and in the formation of plaques [ 33 ]. Hence, it is of great interest how both can be influenced through diet.…”
Section: Introductionmentioning
confidence: 99%